Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1051/parasite/2018001
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum, Dirofilaria spp. and other endoparasite infections in kennel dogs in central Italy

Abstract: Prevalence and risk factors of Leishmania infantum, Dirofilaria spp. and other potentially zoonotic or canine-specific endoparasite infections were assessed in 639 kennel dogs from central Italy. To this end, individual blood and fecal samples were examined using parasitological, immunological and molecular techniques. The presence of compatible clinical pictures, as well as age and gender were considered as putative risks factors. To evaluate risk factors, multivariable analysis with logistic regression and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
(75 reference statements)
8
28
2
Order By: Relevance
“…The prevalence of G. duodenalis in primary CE found in the present study (34%) is much higher than data reported in recent studies in symptomatic dogs in Europe (Epe et al, 2010;Volkmann et al, 2017). Furthermore, it is higher than prevalence of G. duodenalis found in different dog populations in Italy (Pipia et al, 2014;Zanzani et al, 2014;Paoletti et al, 2015;De Liberato et al, 2018), including privately owned (about 4%) and kennel (about 5%) dogs of the same area (Riggio et al, 2013;Sauda et al, 2018). In our opinion, this high prevalence which we found it is unlikely to be associated to a primary G. duodenalis infection.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of G. duodenalis in primary CE found in the present study (34%) is much higher than data reported in recent studies in symptomatic dogs in Europe (Epe et al, 2010;Volkmann et al, 2017). Furthermore, it is higher than prevalence of G. duodenalis found in different dog populations in Italy (Pipia et al, 2014;Zanzani et al, 2014;Paoletti et al, 2015;De Liberato et al, 2018), including privately owned (about 4%) and kennel (about 5%) dogs of the same area (Riggio et al, 2013;Sauda et al, 2018). In our opinion, this high prevalence which we found it is unlikely to be associated to a primary G. duodenalis infection.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, only the canine assemblages C and D were identified at genotyping of some dog fecal samples found positive for G. duodenalis at molecular analysis. These data seem to confirm the higher frequency of these canine-specific assemblages in privately owned dogs in Italy (Pipia et al, 2014;Paoletti et al, 2015;Simonato et al, 2017;Sauda et al, 2018). Nevertheless, it is not possible to exclude the presence of the zoonotic assemblages A and B in the remaining positive dog samples for which molecular analysis and genotyping were not possible.…”
Section: Discussionmentioning
confidence: 74%
“…The southward changing pattern of HW has been detailed in previous studies [26][27][28][29]. Hyperendemic D. immitis infection has been recorded in sheltered dogs from Apulia region (southern Italy) with the highest prevalence of infection (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…The southward changing pattern of HW has been detailed in previous studies [26][27][28][29]. A recent questionnaire study pointed out Brindisi and Lecce, from Apulia region, to be areas with more than 20 cases of HW caused by D. immitis [30].…”
Section: Resultsmentioning
confidence: 86%